2024
DOI: 10.1038/s41392-023-01693-0
|View full text |Cite
|
Sign up to set email alerts
|

Intratumoural microbiota: a new frontier in cancer development and therapy

Yaqi Cao,
Hui Xia,
Xueyun Tan
et al.

Abstract: Human microorganisms, including bacteria, fungi, and viruses, play key roles in several physiological and pathological processes. Some studies discovered that tumour tissues once considered sterile actually host a variety of microorganisms, which have been confirmed to be closely related to oncogenesis. The concept of intratumoural microbiota was subsequently proposed. Microbiota could colonise tumour tissues through mucosal destruction, adjacent tissue migration, and hematogenic invasion and affect the biolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(4 citation statements)
references
References 345 publications
0
4
0
Order By: Relevance
“…In essence, the influence of locally resident microbiota or intratumor microbiota on cancer therapy remains inadequately explored ( 115 ). Although the roles of certain locally resident or intratumor bacteria have been confirmed in select cases, the majority of studies have focused on gut-related scenarios.…”
Section: Current Challenges - the Intratumor Microbiotamentioning
confidence: 99%
“…In essence, the influence of locally resident microbiota or intratumor microbiota on cancer therapy remains inadequately explored ( 115 ). Although the roles of certain locally resident or intratumor bacteria have been confirmed in select cases, the majority of studies have focused on gut-related scenarios.…”
Section: Current Challenges - the Intratumor Microbiotamentioning
confidence: 99%
“…Initially, it was thought that the tumor microenvironment, besides the tumor cells, comprised all the immune cells, chemokines, cytokines, and other molecules or cells present in the local environment. Currently, thanks to the advancements in next-generation sequencing and bioinformatic technologies, researchers have found new evidence regarding the microbiome’s role in modulating the tumor phenotype in some cancers, as well as modulating growth, inflammation, the immune system response, genome instability, and therapy resistance [ 38 , 40 , 41 ]. In 2022, the hallmarks of cancer were updated by Hanahan adding other factors that could influence the tumor, including polymorphic microbiomes [ 12 ].…”
Section: Microbiota’s Importance In Tumor Microenvironmentmentioning
confidence: 99%
“…Indeed, several studies reported that changes in tissue-specific microbiota are related to malignant transformation in these tissues [ 38 , 43 , 44 , 45 , 46 ]. It was demonstrated that some bacteria, such as Fusobacterium nucleatum , interfere with some molecular pathways involved in tumorigenesis, triggering the invasiveness potential of the cells, through modifications in cell–cell adhesion driving the epithelial-to-mesenchymal transition (EMT) process, which represents an important step in some physiological processes and in tumorigenesis [ 41 , 47 ]. In detail, a Fusobacterium nucleatum adhesin named FadA can bind to E-cadherin on tumor cells of the gut epithelium, modulating E-cadherin/β-catenin signaling, which results in more available molecules of β-catenin, triggering the EMT process leading to the invasiveness potential of the cells and ultimately increasing some oncogenes expression [ 48 , 49 ].…”
Section: Microbiota’s Importance In Tumor Microenvironmentmentioning
confidence: 99%
See 1 more Smart Citation